Healing as/or forgiveness? The use of the term 'rfʾ' in the book of Hosea - O'Kennedy, D. F. (Old Testament essays, 2001)
The term רפא conveys different meanings in the Old Testament and is translated as follows: heal, restore, mend, repair, and cure, etc. The verb רפא occurs five times in the book of Hosea: (5:13; 6:1; 7:1; 1l:3; and 14:5 [4]) and all these references are translated into the word 'heal '. A few questions may be posed: How do we understand the meaning of the word 'heal'? Do we understand it literally or in a more 'figurative' or 'spiritual' sense? Can we make a sharp distinction between the 'literal' and 'figurative' use of the term רפא? According to the book of Hosea healing is more than a medically verifiable physical process. The רפא verses in Hosea refer to a deeper dimension of healing. This article discusses the 'deeper' dimension of the verb רפא in the book of Hosea and poses the question whether the רפא references in Hosea convey the meaning of forgiveness or not. In the strict sense of the word merely one רפא verse refers to divine forgiveness: 'I will heal their disloyalty' (Hos 14:5 [4]). Several reasons are offered motivating this viewpoint. On the other hand healing and forgiveness do not stand in opposition to each other. Healing could also be understood as forgiveness.